Oral Hygiene Behavior and Periodontal Disease Status of Fishpond Community - Loviana, Narita Ajeng; Yani, Ristya Widi Endah (Humanistic Network for Science and Technology (Address: Cemara street 25, Ds/Kec Sukorejo, Ponorogo, East Java, Indonesia 63453), 2018)
-